Nature, Power, and Poetry: Unveiling Ecofeminist Narratives in Rena Priest's Green Literary Movement - Winarti, Winarti (Buana Gender: Jurnal Studi Gender dan Anak, 2024)
In an era marked by increasing ecological devastation and the intensification of social injustices, literature becomes a vital tool in terms of exploring the interwoven systems of environmental destruction and patriarchal oppression. While Rena Priest's poetry has been acknowledged for its eco-centric narratives, how it relates to ecofeminist thought has yet to receive adequate scrutiny. The following research strives to fill this gap by exploring how Priest's work—Tour of Salmonberry, The Index, and The Forest for the Trees—articulate a critique of dominant patriarchal and capitalist ideologies through the lens of ecofeminism. Through a descriptive qualitative research methodology, the research employs close reading methods to unveil the imagery, language, and symbols by which Priest's poetry conveys messages of resilience, interconnection, and Indigenous ecological knowledge. Priest's poetry goes beyond simple representation of powerful natural forces; it also speaks to silenced communities—most notably women and marginal communities—through the empowering voice of poetry. The research shows that Priest's work contributes to the green literary movement by promoting vital conversations with the natural world, disrupting hierarchical binarism, and promoting integrated somatic ecological justice. The research contributes to the broader ecofeminist discourse in literary study by showing how poetry has the power to serve as a force of change to deconstruct and renegotiate relations between humanity and nature, society, and existing power orders.